On the Category of EQ-algebras - Akhlaghinia, Narges; Aaly Kologani, Mona; Borzooei, Rajab Ali; Xin, Xiao Long (Bulletin of the Section of Logic, 2021)
In this paper, we studied the category of EQ-algebras and showed that it is complete, but it is not cocomplete, in general. We proved that multiplicatively relative EQ-algebras have coequlizers and we calculated coproduct and pushout in a special case. Also, we constructed a free EQ-algebra on a singleton.